The Effect of Physical Stress on the Quality of Mouse Sperm (Mus Musculus L.) Adult Males - Grace Hanna Christian; Juminten Saimin; Tomy Nurtamin (International Journal Labs, 2023)
Physical stress is one cause that can affect sperm quality. Vibration exposure as a form of physical stress that can stimulate the hormonal system so that it can disturb the process of spermatogenesis which consequently can decrease quality of sperm. This was a true experimental research with post test only control group design was done in the Integrated Laboratory of the Faculty of Medicine Halu Oleo University. Samples was 28 mice (Mus musculus L.) adult male, it were divided into 4 groups: control group (K), the treatment group 7 minutes 30 second (P1), 15 minutes (P2) and 30 minutes (P3) with the vibrations of 50 Hz for 21 days. Sperm quality include motility, viability, concentration and morphology. Data were analyzed descriptively test and Fisher's test. The results of this study indicated the significant differences (p<0,05) to quality of spermatozoa of adult mice.The conclusion of this study was vibration exposure at 50 Hz in the duration of 7 minutes 30 seconds, 15 minutes and 30 minutes for 21 days can decreased quality of sperm. It was suggested for further research can examined the levels of testosterone and histology on Leydig cells and Sertoli cells of the testis.